Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpls.2020.610591
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Phosphorus Concentration Regulates the Development of Cluster Roots and Exudation of Carboxylates in Macadamia integrifolia

Abstract: Phosphorus (P) deficiency induces cluster-root formation and carboxylate exudation in most Proteaceae. However, how external P supply regulates these root traits in Macadamia integrifolia remains unclear. Macadamia plants were grown hydroponically with seven P levels to characterize biomass allocation, cluster-root development, and exudation of carboxylates and acid phosphatases. Plant biomass increased with increasing P supply, peaking at 5 μM P, was the same at 5–25 μM P, and declined at 50–100 μM P. Leaf P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…Generally, leaf nitrogen content in grasses should not exceed 3.5% [ 33 ]; thus, our findings showed safe values. Leaf phosphorus content in grasses does not usually exceed 0.7–0.8% [ 34 ], which agrees with our findings, whereas leaf potassium content can range between 1.2 and 2.0% [ 35 ]. This simulates that the selected grasses may show some K deficiency.…”
Section: Discussionsupporting
confidence: 90%
“…Generally, leaf nitrogen content in grasses should not exceed 3.5% [ 33 ]; thus, our findings showed safe values. Leaf phosphorus content in grasses does not usually exceed 0.7–0.8% [ 34 ], which agrees with our findings, whereas leaf potassium content can range between 1.2 and 2.0% [ 35 ]. This simulates that the selected grasses may show some K deficiency.…”
Section: Discussionsupporting
confidence: 90%
“…The phosphorus absorption efficiency (PAE) is very useful for providing plants with a high phosphorus efficiency [30]. It has been reported that the correlation analysis between plant P content and plant biomass showed that the phosphorus absorption content was positively correlated with the plant's growth [35,36]. Our results showed that invasive Wedelia had a lower PAE decrease ratio than native Wedelia under various P forms and growth stages.…”
Section: Discussionmentioning
confidence: 55%
“…Inclusion of E. todtiana also increased CR production and the CR‐to‐non‐CR ratio in B. menziesii . Taken together, these results reflected the greater demand to mobilise P of B. menziesii in the mixture when E. todtiana competed for some of the mobilised P (Zhao et al ., 2021). Conversely, the significant increase in biomass and leaf P content without alteration of root‐to‐shoot ratio of E. todtiana indicated its P status was enhanced by facilitation by the carboxylate‐releasing P‐mobilising B. menziesii .…”
Section: Discussionmentioning
confidence: 99%